Shedding Light on Sustainable Shipping: Examining Content and Motivations for Sustainability Reporting along the Shipping Value Chain - Bakken,Christian Andrew (IIIEE Master Thesis, 2021)
Sustainability reporting is the primary way corporate sustainability data is disseminated to stakeholders and the wider public. While sustainability reporting is growing, certain industries still lag, such as shipping. Given the crucial role sustainability reporting can play in driving sustainable business practices, promoting improved reporting in the shipping industry is a valuable goal. This thesis examines the main factors characterizing and motivating sustainability reporting within shipping in order to identify focal areas for strengthened sustainability reporting. The thesis looks not only at shipping lines but other industry actors to analyze the interactions between different players in the shipping value chain. This study consists of two analyses. The first reviews the published sustainability material of companies involved in the shipping industry to explore the prevalence of key sustainability themes and frameworks. The second consists of interviews with sustainability leadership at firms within the shipping value chain to discover deeper insights on the motivations and barriers influencing a company’s sustainability disclosure process. The sustainability reporting analysis revealed a wide range of frameworks used and themes reported on. The most prominent frameworks were the GRI and SDGs. Most reports covered many sustainability themes, but safety and climate-related issues were most prevalent, with less coverage of emerging fields such as natural capital valuation. Interviews pointed to the key role cargo owners play in driving sustainable practices and data collection in shipping lines as well as the value of regulatory action and growing interest from diverse stakeholder groups in sustainability reporting, but that greater standardization in reporting demands would ease their burden and improve consistency. Overall, this thesis shows that the current status of shipping sustainability reporting is very diverse and industry-wide coordination could fill current gaps and allow for diffusion of existing best practices.
Keywords: Sustainability Reporting; Shipping; Value Chain Analysis; Stakeholders